Spontaneous cancer remission after COVID-19: insights from the pandemic and their relevance for cancer treatment - Concetta Meo; Giuseppe Palma; Francesca Bruzzese; Alfredo Budillon; Claudio Napoli; Filomena de Nigris (Journal of Translational Medicine, 2023)
Abstract Early in the COVID-19 pandemic, it emerged that the risk of severe outcomes was greater in patients with co-morbidities, including cancer. The huge effort undertaken to fight the pandemic, affects the management of cancer care, influencing their outcome. Despite the high fatality rate of COVID-19 disease in cancer patients, rare cases of temporary or prolonged clinical remission from cancers after SARS-CoV-2 infection have been reported. We have reviewed sixteen case reports of COVID-19 disease with spontaneous cancer reduction of progression. Fourteen cases of remission following viral infections and two after anti-SARS-CoV-2 vaccination. The immune response to COVID-19, may be implicated in both tumor regression, and progression. Specifically, we discuss potential mechanisms which include oncolytic and priming hypotheses, that may have contributed to the cancer regression in these cases and could be useful for future options in cancer treatment.